Rapid and sensitive detection of Candidatus Liberibacter asiaticus by loop mediated isothermal amplification combined with a lateral flow dipstick - Rigano, Luciano Ariel (2014)
Background: Citrus Huanglongbing (HLB) is the most devastating bacterial citrus disease worldwide. Three Candidatus Liberibacter species are associated with different forms of the disease: Candidatus Liberibacter asiaticus, Candidatus Liberibacter americanus and Candidatus Liberibacter africanus. Amongst them, Candidatus Liberibacter asiaticus is the most widespread and economically important. These Gram-negative bacterial plant pathogens are phloem-limited and vectored by citrus psyllids. The current management strategy of HLB is based on early and accurate detection of Candidatus Liberibacter asiaticus in both citrus plants and vector insects. Nowadays, real time PCR is the method of choice for this task, mainly because of its sensitivity and reliability. However, this methodology has several drawbacks, namely high equipment costs, the need for highly trained personnel, the time required to conduct the whole process, and the difficulty in carrying out the detection reactions in field conditions. Results: A recent DNA amplification technique known as Loop Mediated Isothermal Amplification (LAMP) was adapted for the detection of Candidatus Liberibacter asiaticus. This methodology was combined with a Lateral Flow Dipstick (LFD) device for visual detection of the resulting amplicons, eliminating the need for gel electrophoresis. The assay was highly specific for the targeted bacterium. No cross-reaction was observed with DNA from any of the other phytopathogenic bacteria or fungi assayed. By serially diluting purified DNA from an infected plant, the sensitivity of the assay was found to be 10 picograms. This sensitivity level was proven to be similar to the values obtained running a real time PCR in parallel. This methodology was able to detect Candidatus Liberibacter asiaticus from different kinds of samples including infected citrus plants and psyllids. Conclusions: Our results indicate that the methodology here reported constitutes a step forward in the development of new tools for the management, control and eradication of this destructive citrus disease. This system constitutes a potentially field-capable approach for the detection of the most relevant HLB-associated bacteria in plant material and psyllid vectors.